2018
DOI: 10.3390/ma11030386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Temperature on the Structural and Electrical Properties of ZrO2 Films Fabricated by Atomic Layer Deposition Using a CpZr[N(CH3)2]3/C7H8 Cocktail Precursor

Abstract: The effect of growth temperature on the atomic layer deposition of zirconium oxide (ZrO2) dielectric thin films that were fabricated using a CpZr[N(CH3)2]3/C7H8 cocktail precursor with ozone was investigated. The chemical, structural, and electrical properties of ZrO2 films grown at temperatures from 250 to 350 °C were characterized. Stoichiometric ZrO2 films formed at 250–350 °C with an atomic ratio of O to Zr of 1.8–1.9 and a low content of carbon impurities. The film formed at 300 °C was predominantly the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In order to prove this hypothesis, we conducted control experiment by making a ZrO 2 layer on LaAlO 3 through oxidation of sputter-deposited Zr metal thin films. Magnetic measurement revealed clear MH loops from 10 to 400 K, suggesting that the T c of ZrO 2 is at least higher than 400 K (see details in Figure S5 and Supplementary Note 2), which is consistent with previous reports of ZrO 2 showing high-temperature ferromagnetism up to 700 K. In addition, the differences in magnetic results of the heterostructure with those of the YIG indeed suggest additional ferromagnetic contribution (see Figure S6). Moreover, the YIG-induced AHE in TMDs and topological materials are usually with an observation temperature much lower than T c of YIG, , and the R AHE is small.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In order to prove this hypothesis, we conducted control experiment by making a ZrO 2 layer on LaAlO 3 through oxidation of sputter-deposited Zr metal thin films. Magnetic measurement revealed clear MH loops from 10 to 400 K, suggesting that the T c of ZrO 2 is at least higher than 400 K (see details in Figure S5 and Supplementary Note 2), which is consistent with previous reports of ZrO 2 showing high-temperature ferromagnetism up to 700 K. In addition, the differences in magnetic results of the heterostructure with those of the YIG indeed suggest additional ferromagnetic contribution (see Figure S6). Moreover, the YIG-induced AHE in TMDs and topological materials are usually with an observation temperature much lower than T c of YIG, , and the R AHE is small.…”
Section: Resultssupporting
confidence: 89%
“…The ZrO 2 layer is a high- k insulator, and it does not contribute to any electrical signals. During the past decade, both experimental and theoretical studies have shown that intrinsic defects in the oxide nanomaterials can lead to room-temperature ferromagnetism. A recent paper reported that oxygen vacancy defect-rich ZrO 2 nanostructures show high T c (700 K) and high magnetization (5.9 emu/g) . It should be noted that the deposition process of ZrTe 2 takes place in a high vacuum environment, and therefore, the ZrO 2 layer formed under such a process should be rich in oxygen vacancies, which are possibly responsible for the magnetic moments.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, HfO 2 has been studied to replace conventional SiO 2 as a high-κ material because of its advantages, such as high density, good ductility and corrosion resistance, as well as its high-k [3,4]. HfO 2 has mainly been deposited by thermal atomic layer deposition (thermal ALD) because this method produces thin films that are pinhole-free, high density and have low contaminants levels (Carbon, Nitrogen); this process also allows excellent thickness control [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The growth rate decreased due to precursor desorption by too high a temperature of 400 °C, which prevented the formation of ZrO 2 . [ 20,21 ] This means the crystallinity may be low. Crystallographic data are a key factor in determining plasma power's effect on ZrO 2 thin films’ dielectric constant because the films have identical peaks and only differ in peak intensity.…”
Section: Resultsmentioning
confidence: 99%